A STUDY OF PRO-ENVIRONMENTAL ATTITUDE: ITS ANTECEDENTS AND CONSEQUENCES - Jayananda, Aurelia; Ekasari, Ayu (Jurnal Ekonomi Trisakti, 2024)
This study examines the factors influencing pro-environmental behavior in Indonesia, focusing on emotional, functional, and relational values, and environmental concerns. The research objectives of this research are to analyze the influence of emotional value, functional value, relational value, and environmental concern on pro-environmental attitudes. A quantitative research design employing surveys was used to gather data from Indonesian respondents. The findings indicate positive influence of emotional value, relational value, and environmental concern, on pro-environmental attitudes; however functional value did not have a significant influence. Additionally, pro-environmental attitudes were found to positively influence intentions to conserve resources. These insights provide actionable strategies for fostering a more environmentally conscious society, supporting Indonesia's sustainability goals. Moreover, the study examines how pro-environmental attitudes influence conservation intentions. The results highlight the importance of these values and attitudes in shaping pro-environmental behavior, offering valuable guidance for institutions, educators, and marketers aiming to promote sustainability in Indonesia.